Peran Pendidikan Kewarganegaraan dalam Membangun Toleransi di Lingkungan Mahasiswa - Khofifah Hera Wenzana; Hanina Nafilah; Melda Novitasari; Nur Hafizah; Alfira Nur Adella; Dhea Meiza Azzahra (International Forum of Researchers and Lecturers, 2024)
This research aims to analyze how the level of tolerance between students and find out the extent of the implementation of PKN (civic education) in building an attitude of tolerance in the student environment. By using the literature approach method which is certainly relevant to the research topic. Involving 17 journal articles published between 2020 and 2023, this research aims to identify the main things about tolerance that exist in the student environment. And from this research can be the basis for building the nature of tolerance in the student environment through the role of civic education. With the nature of tolerance, students are more able to respect different opinions and can interact with people from various cultural, religious and ethnic backgrounds.